Relational Mobility and Other Contributors to Decline in Intimate Partner Violence. Issue 21 (November 2022) - Hashemi, Ladan; Fanslow, Janet L.; Gulliver, Pauline; McIntosh, Tracey
This study explored whether changes in risk and protective factors of intimate partner violence (IPV) can account for the noted reduction in 12-month IPV prevalence in New Zealand between 2003 and 2019. Changes in relational mobility over time were also explored. Data from two population-based surveys of 18-64 year-old ever-partnered women in New Zealand that were conducted according to identical procedures in 2003 (n=2764) and 2019 (n=944) were used. Changes in a variety of potential risk and protective factors over time and their possible contribution to IPV reduction were assessed. The findings indicated that there was no change in the prevalence of the strongest risk and protective factors of IPV victimisation and perpetration over time (e.g. partner concurrent relationship, previous exposure to violence for both respondent and partner, and partner's problematic alcohol/drug use). However, a combination of factors including decline in women's problematic alcohol or drug use, decline in the number of children within families, and increases in the proportion of women and partners with a qualification higher than secondary education are likely to be associated with the reduction in IPV prevalence. A greater degree of relational mobility, demonstrated through a greater proportion of women who left their abusive partner permanently and increased numbers of relationships that women had, was also observed between two study years. Overall, these results indicate that changes in 12-month IPV prevalence over time are likely to be linked with changes that increase women's autonomy and ability to move out of violent relationships. To achieve sustained reductions in IPV, more comprehensive and planned efforts are needed to address other underlying and exacerbating causes, including problematic alcohol/drug use and previous exposure to violence during childhood and adulthood.